5-Aryl-1H-pyrazole-3-carboxylic acids as selective inhibitors of human carbonic anhydrases IX and XII. Issue 15 (1st August 2015) - Cvijetić, Ilija N.; Tanç, Muhammet; Juranić, Ivan O.; Verbić, Tatjana Ž.; Supuran, Claudiu T.; Drakulić, Branko J.
Graphical abstract: Abstract: Inhibitory activity of a congeneric set of 23 phenyl-substituted 5-phenyl-pyrazole-3-carboxylic acids toward human carbonic anhydrase (hCA, EC 4.2.1.1) isoforms I, II, IX and XII was evaluated by a stopped-flow CO2 hydrase assay. These compounds exerted a clear, selective inhibition of hCA IX and XII over hCAI and II, with K i in two to one digit micromolar concentrations (4–50 μM). Derivatives bearing bulkier substituents in para -position of the phenyl ring inhibited hCA XII at one-digit micromolar concentrations, while derivatives having alkyl substituents in both ortho - and meta -positions inhibited hCA IX with K i s ranging between 5 and 25 μM. Results of docking experiments offered a rational explanation on the selectivity of these compounds toward CA IX and XII, as well as on the substitution patterns leading to best CA IX or CA XII inhibitors. By examining the active sites of these four isoforms with GRID generated molecular-interaction fields, striking differences between hCA XII and the other three isoforms were observed. The field of hydrophobic probe (DRY) appeared significantly different in CA XII active site, comparing to other three isoforms studied. To the best of our knowledge such an observation was not reported in literature so far. Considering the selectivity of these carboxylates towards membrane-associated over cytosolic CA isoforms, the title compounds could be useful for the development of isoform-specific non-sulfonamide CA inhibitors.